All or nothing: the interaction of musical and spatial atmosphere - Ehret, Sonja; Schroeder, Carolin; Bernet, Johannes; Holzmüller, Anne; Thomaschke, Roland (2019)
Abstract: Atmosphere can be defined as the affective quality of an environment. Prior research has shown that music can influence how an environment is affectively perceived. In the current study, we systematically examined in three experiments how musical and spatial atmosphere interact and influence the overall valence of the atmosphere. In Experiments 1a (n = 50) and 1b (n = 136), we identified two rooms and two musical pieces that strongly contrast in the valence of perceived atmosphere. In Experiments 2 and 3, 32 participants each were exposed to the four combinations of rooms and music for 10-min periods on two different days. Perceived overall atmosphere was assessed. Musical and spatial valence both significantly affected the experienced overall valence of atmosphere. A significant interaction between music and room showed that making one aspect of a perfectly pleasant overall atmosphere negative had a much stronger effect than making one aspect positive in a totally unpleasant atmosphere. This suggests that pleasant atmospheres are particularly vulnerable, which might be explained by an attentional bias toward negative information. Future research should focus on examining fundamental psychological mechanisms underlying the constitution of perceived atmosphere